Meso‐Reconstruction of Wool Keratin 3D "Molecular Springs" for Tunable Ultra‐Sensitive and Highly Recovery Strain Sensors. Issue 24 (11th May 2020) - Zhang, Lin; Hu, Fan; Zhu, Shuihong; Lin, Youhui; Meng, Zhaohui; Yu, Rui; Liu, Xiang Yang
Abstract: Wool keratin (WK) consists of a large number of α‐helices, which are just like many molecular‐scale springs. Herein, the construction of 3D WK molecular spring networks are reported by cross‐linking individual WK molecules via a Michael addition reaction. The as‐prepared springs display a superior recovery capability with unusual nonlinear elasticity, very low dissipative energy, and turntable elastic constant achieved by adjusting the chemical crosslinking density of WK networks. Owing to these unique characteristics, the 3D WK networks based flexible strain sensors reveal a high sensitivity, broad sensing ranges, and extremely long and stable performance. While normal highly sensible strain sensors, obtained by highly sophisticated surface or bulk patterning, often exhibit a relatively narrow range of measurements and limited life cycles. Such the WK mediated sensing materials have widespread applications in wearable electronics, such as detection and tracking of different human motions, and even discern voice during speaking. Abstract : Herein, 3D "molecular springs" networks are successfully created by establishing crosslinks of scattered wool keratin. The as‐prepared networks display unique elasticity, stretchability, high resistance to fatigue, fast self‐recovery, and ultralow effective elastic modulus. Due to these unique characteristics, such wool keratin mediated materials can be used in the construction of reliable and highly sensitive strain sensors with broad sensing ranges.